Cranial Nerve Coactivation and Implication for Nerve Transfers to the Facial Nerve. Issue 4 (April 2018) - Jensson, David; Enghag, Sara; Bylund, Nina; Jonsson, Lars; Wikström, Johan; Grindlund, Margareta; Flink, Roland; Rodriguez-Lorenzo, Andres
Abstract : Summary: In reanimation surgery, effortless smile can be achieved by a nonfacial donor nerve. The underlying mechanisms for this smile development, and which is the best nonfacial neurotizer, need further clarification. The aim of the present study was therefore to further explore the natural coactivation between facial mimic muscles and muscles innervated by the most common donor nerves used in smile reanimation. The study was conducted in 10 healthy adults. Correlation between voluntary facial muscle movements and simultaneous electromyographic activity in muscles innervated by the masseter, hypoglossal, and spinal accessory nerves was assessed. The association between voluntary movements in the latter muscles and simultaneous electromyographic activity in facial muscles was also studied. Smile coactivated the masseter and tongue muscles equally. During the seven mimic movements, the masseter muscle had fewer electromyographically measured coactivations compared with the tongue (two of seven versus five of seven). The trapezius muscle demonstrated no coactivation during mimic movements. Movements of the masseter, tongue, and trapezius muscles induced electromyographically recorded coactivation in the facial muscles. Bite resulted in the strongest coactivation of the zygomaticus major muscle. The authors demonstrated coactivation between voluntary smile and the masseter and tongue muscles. During voluntary bite, strong coactivation of the zygomaticus major muscle was noted. The narrower coactivation pattern in the masseter muscle may be advantageous for central relearning and the development of a spontaneous smile. The strong coactivation between the masseter muscle and the zygomaticus major indicates that the masseter nerve may be preferred in smile reanimation.